The Influence and Factors of Nurse Therapeutic Communication on Patient Satisfaction: A Systematic Review - Mery Angreani Safitri; Nursalam Nursalam; Hanik Endang Nihayati (Indonesian Journal of Global Health Research, 2024)
Important for nurses to have good therapeutic communication skills so that nurses more easily establish trusting relationships with patients, so as to improve the quality of health services provided. Patient satisfaction is an important indicator for healthcare providers. This study aims to determine the influence and factors of nurse therapeutic communication on patient satisfaction. The research design used was a systematic review, the sample used was a hospital nurse, the variables were therapeutic communication and patient satisfaction. The intervention provided was the implementation of good therapeutic communication of the nurse with the patient. Articles searched was using five databases published since 2019 through 2024. A total of 77,254 articles were identified in five databases, after the screening process, those studies that did not meet the criteria were not included in the analysis. A total of 77,254 articles identified were obtained from five databases, namely Pubmed with 1400 articles, Proquest with 13354 articles, Scince Direct with 10,000 articles, Sage Journal with 45,600 articles, and SpringerLink with 6900 articles. The screening process was carried out based on the year of publication of 55,038 articles, filtering based on language as many as 15,816 articles, filtering by type of article as many as 13,147 articles, and duplicate documents as many as 421 articles. Research screening is continued based on the results of titles and abstracts so that 10 articles can be used in systematic reviews. The reason for exclusion is due to the research point of view. Because it does not match the desired criteria. All of them focus on the influence and factors of nurse therapeutic communication on patient satisfaction. There were 10 cross-sectional articles selected involving 43177 patients who rated hospital service satisfaction and 1617 nurses who applied therapeutic communication. Gender, nurse burnout, lack of empathy from nurses, challenging nursing duties, use of technical terms by nurses, lack of trust in nurses, stress, ignorance with nurses' job descriptions, lack of nurses, lack of knowledge, lack of participation in decision making, and infectious diseases showed significant and negative associations with overall therapeutic communication. So that it can affect the level of patient satisfaction. Motivating and creating a positive work environment are essential to improve therapeutic communication. Good nurse therapeutic communication can increase patient satisfaction. Patient satisfaction with the services provided is very important parameter of health service quality.